2019
DOI: 10.1111/cdev.13244
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Teamwork: The Impact of a Fathering Intervention on Mothers and Infants in Vietnam

Abstract: A multifaceted, relationally focused intervention involving group and individual pre‐ and postnatal counseling, print resources, and community resources encouraged 390 fathers of newborn infants in Vietnam to responsively support mothers and work with them as a parenting team. Both partners completed questionnaires prebirth and 1‐, 4‐, and 9‐months postbirth on measures of breastfeeding support, exclusive breastfeeding duration, relationship quality, and infant development. Compared to 412 comparison group cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Further to our analytical inspirations and the literature reviewed here, experiences of paradox (or related concepts of ambivalence and dilemma) have been found in studies on other kinds of children’s illness (e.g., Jones, Parker-Raley, & Barczyk, 2011; Rallison & Raffin-Bouchal, 2013), on congenital anomalies in general (Rempel, 2005), as well as in studies on acquired cardiovascular disease in adults such as heart failure (e.g., Hellesø, Eines, & Fagermoen, 2012; Overgaard, Grufstedt Kjeldgaard, & Egerod, 2012). Particularly on CHDs, authors of a previous study found fathers of newly diagnosed infants with CHDs to experience “conflicting responses,” as they are both happy and sad, want and fear attachment, need control while losing it, and struggle to support others by hiding their own emotions (Clark & Miles, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…Further to our analytical inspirations and the literature reviewed here, experiences of paradox (or related concepts of ambivalence and dilemma) have been found in studies on other kinds of children’s illness (e.g., Jones, Parker-Raley, & Barczyk, 2011; Rallison & Raffin-Bouchal, 2013), on congenital anomalies in general (Rempel, 2005), as well as in studies on acquired cardiovascular disease in adults such as heart failure (e.g., Hellesø, Eines, & Fagermoen, 2012; Overgaard, Grufstedt Kjeldgaard, & Egerod, 2012). Particularly on CHDs, authors of a previous study found fathers of newly diagnosed infants with CHDs to experience “conflicting responses,” as they are both happy and sad, want and fear attachment, need control while losing it, and struggle to support others by hiding their own emotions (Clark & Miles, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…“They developed fun and informative skits, songs, poems, art, or photo displays that demonstrated how a father can show love to his wife by supporting breastfeeding and love for his infant through positive, responsive interactions. By being open to the public, the contest had the potential to further shift community norms about father breastfeeding support and father–infant engagement.” (Rempel et al 59 …”
Section: Resultsmentioning
confidence: 99%
“…By being open to the public, the contest had the potential to further shift community norms about father breastfeeding support and father-infant engagement." (Rempel et al 59 ) "Husbands' forums brought together husbands in the community and gave them opportunities to engage in peer-to-peer discussion on issues related to maternal nutrition and how they could support their wives." (Nguyen et al 56 ) "After the final mentoring session, an open community meeting, or 'community celebration' , took place in each study community and were attended by LC1s [Local Council 1 leaders], program participants, and their wives and families.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study revealed that working together as a parenting team would help EBF succeed. The husband's function was also identified as a predictor of EBF performance in this analysis 21 . According to the findings of a study conducted in Canada, parental collaboration affects awareness, attitudes, and behaviors of exclusive breastfeeding and the length of breastfeeding 22 .…”
Section: Resultsmentioning
confidence: 99%